Оптимизация параметров нечетких ПИД контроллеров - Герман, Эдуард Евгеньевич; Дербунович, Леонид Викторович; Белецкий, С. В. (НТУ "ХПИ", 2007)
В статті запропоновано новий спосіб розбивки нормованої області нечітких функцій для похибки сигналу та керуючого впливу в НПІДК. Обґрунтовані причини такої розбивки. Отримані аналітичні вирази для обчислення залежності uF (e) в нечіткому блоці НПІДК.

In the paper the new way of partitioning of normalized space of fuzzy functions for an error of a signal and control action in FPIDC is proposed. The reasons of such partitioning are justified. The analytical expressions for calculus of relation in the fuzzy unit of FPIDC are obtained.
Keywords: неопределенная информация; возмущающие воздействия; нечеткий логический вывод; функции принадлежности; сигнал ошибки; нечеткий блок